Leader-Member Exchange (LMX) Ambivalence and Task Performance: The Cross-Domain Buffering Role of Social Support. (May 2019) - Lee, Allan; Thomas, Geoff; Martin, Robin; Guillaume, Yves
Leader-member exchange (LMX) theory proposes that leaders develop different quality relationships with those they manage and this is predictive of work performance. While LMX quality has been viewed as univalent (ranging from low to high quality), this paper proposes that it can also be bivalent in nature (i.e., coexisting positive and negative thoughts towards the relationship), which we refer to as LMX ambivalence. A survey measure of LMX ambivalence is developed, and through three validation and two main studies, it is shown to have construct, discriminant, and incremental predictive validity beyond that of LMX quality. Hypotheses concerning LMX ambivalence and task performance are tested in two main studies and show that (1) LMX ambivalence is negatively related to performance regardless of LMX quality, (2) high levels of perceived support from the organization (Study 1) or coworkers (Study 2) nullify the negative association between LMX ambivalence and performance, and (3) high LMX ambivalence leads to more negative affect and in turn lower task performance, but only when coworker support is low (Study 2). These results show the importance of viewing LMX quality not only in terms of its absolute level (low vs. high quality) but also as a bivalent construct where both positive and negative cognitions can coexist. They also demonstrate the value of social support in buffering the negative effects of LMX ambivalence. Furthermore, our findings extend a central tenet of LMX theory by implying that LMX quality varies not only within groups (i.e., LMX differentiation) but also within leader-follower dyads.